Design and Development of Multilevel Inverter for Convert Direct Current to Alternating Current Using MATLAB Simulation - Abu Bakar, Afnan Rusyaidi; Nashiren Farzilah, Mailah; Ibrahim, Abu Bakar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This paper presented the design and development of a multilevel inverter (MLI). The demand for better electronic devices increases rapidly. The multilevel inverter (MLI) which convert direct current (DC) to alternating current (AC) are widely used in the industry. The objective of this research is to design and simulate the 3-level and 3-level NPC MLI module using PLECS software. To develop the switching technique for each level of NPC MLI, and To analyse and validate the MLI in terms of harmonic. Although there is already an inverter in the market, the researcher still pursues to improve the efficiency, total harmonic distortion (THD), and reduce the size of the MLI. An THD can be improved using the suitable modulation technique and the size of the MLI can be reduced by designing better topologies. The modular NPC is using the three-level NPC as the main module and the number of levels can be increased by adding 2 level NPC modules to the main module. The switching technique was created to control the NPC MLI for each level.